Molecular characterization of Cystoisospora belli and unizoite tissue cyst in patients with Acquired Immunodeficiency Syndrome - Velásquez, Jorge Néstor (2011)
Cystoisospora belli is a coccidian protozoan that can cause chronic diarrhoea, acalculous cholecystitis and cholangiopathy in AIDS patients. We applied molecular methods to identify Cystoisospora at species level in AIDS patients presenting with and without the presence of unizoites in lamina propria. Coprological and histological analyses were performed in stool and/or biopsy samples from 8 Cystoisospora-infected patients. DNA from the same samples was used to amplify 2 fragments of the SSU-rRNA gene and the ITS-1 region. Sequencing of the resulting amplicons identified C. belli infections in all cases, independent of the presence or absence of unizoite tissue cysts. Further work should be considered in order to find molecular targets related to strain variations in C. belli.